Role of Micro, Small and Medium Enterprises in Indian Economy - Shelly, Richa; Sharma, Tanuj; Bawa, Simerjeet Singh (International Journal of Economics and Financial Issues, 2020)
The Micro, Small and Medium Enterprises (MSME) are crucial for the economic development of any country and play a pivotal role specifically for developing countries as they regulate economic activity and generate employment thus significantly contribute in poverty reduction. After agriculture, this sector is the second largest employer in India. Indian MSME sector has emerged as dynamic and highly vibrant sector of the economy. MSME, not only play significant role in generating large employment by investing less capital as compared to large industries but also help to develop non-farm sector by increasing industrialization in rural areas. The sector acts as the instrument of inclusive growth empowering the most vulnerable and marginalized groups. The main objectives of the paper are to explore the growth in the number of MSME units, GDP contribution, employment and exports of Indian MSME sector, to analyse the relationship between growth of MSME sector and fulfilment of Sustainable Development Goals (SDGs) 2030, to see the contribution of MSME sector in creating green jobs in India and to highlight the problems of MSME sector. This paper is based on the secondary data extracted from various reports and research papers related to MSME. The time period from 2006-07 to 2016-17 has been taken into consideration. MSME sector is the significant contributor in GDP, employment generation, total exports, achieving SDGs and green development which in turn act as backbone of the Indian economy. Keywords: Micro, Small and Medium Enterprises; Green Jobs; Sustainable Development Goals; Economic Development; Inclusive Growth JEL Classifications: O120; Q560; Q01; O100; O400 DOI: https://doi.org/10.32479/ijefi.10459